СПОСОБИ ПОКРАЩЕННЯ СПЕКТРУ ВХІДНОГО СТРУМУ КОРЕКТОРА КОЕФІЦІЄНТА ПОТУЖНОСТІ - Рогаль, В.В.; Демченко, Ю.С. (Інститут електродинаміки НАН України, Київ, 2015)
The paper shows the negative impact of high current harmonics on the mains supply and the equipment connected to it. The investigation of the performance of the active high-frequency power factor corrector with peak current control method is conducted. In the MATLAB/Simulink environment the model of this corrector is built. The diagrams of the corrector’s input current and its spectrum are given. It was discovered that the value of the third harmonic in the input current spectrum is quite significant. The reason of the appearance of this harmonic is indicated. Methods of power factor corrector input current spectrum improvement are offered and their comparative analysis is conducted. References 8, figures 7.